THE INFLUENCE OF USING THE TIKTOK APP ON THE LANGUAGE DEVELOPMENT OF CHILDREN AGED 5-10 YEARS IN PEMATANG SIANTAR - Damanik, Olivia; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2025)
The rapid growth of digital platforms has transformed the way children access information and engage with media, with TikTok emerging as a significant influence, even among children aged 5–10 years. This study investigates the impact of TikTok on language development in this age group, focusing on vocabulary acquisition, communication skills, and social interaction. Using a qualitative research design, including observations and interviews with parents and educators, the study examines the dual outcomes of TikTok usage. Findings reveal that TikTok contributes positively by expanding vocabulary and encouraging creative expression. However, challenges include a dominance of informal language forms, reduced opportunities for meaningful verbal interactions, and potential dependency on visual and auditory stimuli. The study underscores the importance of balancing TikTok use with structured language learning methods to optimize its educational potential while mitigating its drawbacks. Insights from this research aim to guide parents, educators, and policymakers in fostering constructive digital media use among young children.